METHODS OF APPLYING FERTILIZERS IN PRECISION AGRICULTURE - G. I. Lichman; S. A. Belykh; A. N. Marchenko (Сельскохозяйственные машины и технологии)
It is impossible to achieve the planned yields, product quality, and economic efficiency in agricultural production using only organic fertilizers. joint application of organic and solid mineral fertilizers solves the problem of replenishing the soil content of nitrogen, phosphorus and other elements used by plants. The authors have carried out the research of new methods of variable-rate application of mineral fertilizers in plant growing, allowing to increase the profitability of agricultural production. (Research purpose) is to develop new methods of variable-rate application of mineral fertilizers in crop production, which will allow increasing the profitability of crop production as compared with the conventional methods of applying fertilizers basing on average field indicators.  (Materials and methods) The authors have developed a calculation technique implemented in the VBA Excel computer program for determining the main indicators: gross output, fertilizer saving, profit, etc. The main variable to change in the calculations is the planned yield based on average field parameters. At the end of the calculation process, the values of the best result for gross harvest output and profit are displayed on the screen. The research objects for the calculation were represented by elementary areas of crop areas of three farms – “Prodresurs”, Agropoligon VIUA, and “Murminskoye” with different soil types: chernozem, loamy, and sandy-loam.  (Results and discussion) The method of proportional variable-rate application of fertilizers on three types of soils gives a stable increase in profit as compared with the application of fertilizers basing on the average field indicators. (Conclusions) Calculations  have shown that under the specified conditions and at the equal yield of 30 c/ha the application of organomineral fertilizers is the most effective, profitability has accounted for 40 percents – on mesopodzol sandy-loam soils; 8.7 percents – on sod-podzolic soils; and 1.3 percents – on black soils. The method of proportional variable-rate application of mineral fertilizers accompanied with variable-rate application of organic fertilizers makes it possible to reduce the amount of mineral fertilizers applied by half.